Digital Financial Literacy as a Determinant of Financial Management of MSMEs in Lalabata District - Mutmainna Andi Sudirman; Andi Sonia; Masyadi Masyadi; Sukma Aini (GENTARA: management and accounting research, 2026)
This study aims to analyze the effect of digital financial literacy on financial management of UMKM in Lalabata District. UMKM play a significant role in supporting local economic development; however, many UMKM actors still face challenges in managing their business finances effectively. Along with the rapid development of financial technology, digital financial literacy has become an important factor in improving financial management practices.This study employs a quantitative explanatory approach. Data were collected through a structured questionnaire distributed to 15 UMKM actors using probability sampling techniques. Digital financial literacy was measured through indicators of financial knowledge, savings, insurance, and investment, while financial management was measured through fund allocation, income determination, risk management, and future financial planning. The data were analyzed using simple linear regression with the assistance of SPSS.The results indicate that digital financial literacy has a positive and significant effect on financial management of UMKM. UMKM actors with higher levels of digital financial literacy tend to demonstrate better financial management practices, including more structured budgeting, improved cash flow control, and more systematic financial planning. However, understanding of digital financial products related to insurance and investment remains relatively limited. This study is expected to provide empirical evidence for policymakers and related institutions in designing more effective digital financial literacy programs to support UMKM sustainability in the digital era.